Factors influencing financial inclusion through banking services - Nandru, Prabhakar; Byram, Anand; Rentala, Satyanarayana (Journal of Contemporary Research in Management (JCRM), 2016)
This article aims to investigate the factors that affect the usage of banking services in increasing financial inclusion in Pondicherry region. Purpose of opening bank account, easiness in accessing a bank’s products, convenience, frequency of usage of banking services and physical distance of bank branch were examined to analyse whether these factors have an influence on usage of banking services. Analysis of primary data using factor analysis and multiple regression analysis was undertaken to understand the relationship between dependent variable (Usage frequency of banking services) and other independent variables. The results indicate that easiness in accessing bank products and purpose of opening bank account have significant influence on usage frequency of banking services. Physical distance of bank branch and convenience were not found to have significant impact on usage of banking services in this study. The methodology adopted in this study can be used for further empirical investigation in other regions in India.